Le congréganiste hors la société ? Les dynamiques de laïcisation de la « République radicaliste » au prisme d’une approche d’anthropologie politique (France, 1902-1906) - Julien Bouchet (Amnis)
At the beginning of the twentieth century, France saw a period of republican progress, known as the « Belle Époque ». This period reintroduced the discourse regarding the extent of religious groups’ role in society. This article deals with the exclusion of religious people from positions within the political system. As a result, the Left secularized the parliament and ostracised these religious groups altogether through their social practices and limited membership in several essential government entities (« the Congregation » and « the black party »). The extremism of this commitment created the foundation for a new social contract in which the political authorities would restrict the civil capacity of religious people, by forbidding them to teach and seeking an « exit of religion ». The difficult implications of this ideological act required the State to reconsider its relations with intermediate bodies and discuss the teleological thesis of this trial secularization, which would have prevailed in France with little dissent.